واقع الصيرفة الإسلامية في الجزائر بين العراقيل وسبل التفعيل -دراسة ميدانية لبنوك ولاية الوادي 2018/2022 - - إبراهيم, ترشة; الصادق, جاب الله; عبد القادر, سويسي (جامعة الوادي - University of Eloued, 2023)
"هدفت هذه الدراسة الى معرفة واقع الصيرفة الإسلامية في الجزائر وأهـم المعوقات والمتطلبـات الواجب توفرها لتطوير عملها، معتمدين في ذلك على المنهج الوصفي التحليلي والمقابلة كأداة رئيسة لجمع المعلومات والبيانات الضرورية حيث أجريت دراسة ميدانية لعينة من البنوك والنوافذ الإسلامية المتواجدة على مستوى ولاية الوادي حيث قمنا بزيارة الى معظم الوكالات البنكية المرخصة بتقديم منتجات إسلامية عبر شبابيكها ومن خلال مقابلات مع مسؤولي وموظفي هذه البنوك. وتوصلنا من خلال النتائج المتحصل عليها أن الجهود المبذولة والمساعي الحثيثة بإصدار نظام 20-02 المتعلق بالعمليات الصيرفة الإسلامية وقواعد ممارستها من قبل السلطات يعد خطوة تثبت جديتها في هذا المسعى، إلا أنه لا بد من القيام بالمزيد من الإصلاحات وإدخال التعديلات الجذرية من أجل تفعيل نشاط الصيرفة الاسلامية ومن أهم هذه التعديلات تنظيم علاقة المصارف والنوافذ الإسلامية مع بنك الجزائري."" To further examine this reality, it is important to evaluate the economic, social and political context in which these banks operate. This evaluation should encompass how the banking sector affects the well-being of the population, as well as how it contributes to the economic and social development of the country. The purpose of this study is to determine the reality of Islamic banking in Algeria. To achieve this, we visited most of the public or private banks licensed to provide Islamic products through their branches or banking windows. It was conducted during interviews with officials and employees of these banks that the necessary data and information was collected about this subject. As a result, we were able to achieve several motivating results. Islamic banking operations and its rules of practice are the subject of Regulation 20-02 which proves the authorities' seriousness in this endeavor. Nevertheless, more reforms and radical amendments must be made to activate Islamic banking in the country, and one of the most important of these amendments involves the regulation of Islamic banks' relationship with the Algerian Bank."
Keywords: الصيرفة الإسلامية، النوافذ الإسلامية، الوكالات البنكية، ولاية الوادي.; Islamic banking, Islamic windows, banking agencies, El-Wadi state